“WAS IT GOOD ENOUGH?”: THE ACTUAL AND EXPECTED PERSPECTIVE ON FEEDBACK IN UNDERGRADUATE FORMATIVE ASSESSMENT - Sylvia Mustika Sari; Iis Inayati; Gandes Retno Rahayu (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2022)
Background: In the undergraduate setting, formative assessment is mainly done during learning activities. Feedback is the essential part of formative assessment to facilitate self-regulation learning. This concept needs to consider by both sides, teacher and students. This study explores the undergraduate students’ and teachers’ perspectives on actual and expected feedback in formative assessment.Methods: We conducted a qualitative with a phenomenology approach. Data collection was saturated in seven FGDs (N=56) from undergraduate students and twelve in-depth interviews with teachers. The transcribed data from teachers and students were coded and categorized separately. Finally, we combined the categories from teachers and students to interpret the subthemes and themes.Results: We found students’ perceived the actual feedback as the ‘daily score’, teachers’ explanation, and influenced by teachers’ characters. The expected feedback from students represents the need for 'room' to speak, be more objective, and use "kind" language. Meanwhile, teachers perceived feedback as the obligation to fill the score, give direction about learning goals and describe students’ attitudes. Teachers expect students to be more active in feedback seeking and standardization of feedback content. Therefore, we identified the themes representing 'from the actual to expected' feedback experience in formative assessment, such as (1) From 'daily score' to the objective description of performance; (2) From teachers' explanation to the student's room to speak; (3) From teachers’ authority to teachers’ beneficence.Conclusion: Our study showed the teachers' and students' perceptions of actual and expected feedback experiences. The results describe the awareness of a better feedback form in formative assessment. Further studies can explore more participatory research to lead to a collaborative and bidirectional feedback approach